Bactericidal Activity of Carvacrol against Streptococcus pyogenes Involves Alteration of Membrane Fluidity and Integrity through Interaction with Membrane Phospholipids - Niluni M. Wijesundara; Song F. Lee; Zhenyu Cheng; Ross Davidson; David N. Langelaan; H. P. Vasantha Rupasinghe (MDPI AG, 2022)
Background: Carvacrol, a mono-terpenoid phenol found in herbs, such as oregano and thyme, has excellent antibacterial properties against Streptococcus pyogenes. However, its mechanism of bactericidal activity on S. pyogenes has not been elucidated. Objectives: This study investigated the bactericidal mechanism of carvacrol using three strains of S. pyogenes. Methods: Flow cytometry (FCM) experiments were conducted to determine carvacrol's membrane permeabilization and cytoplasmic membrane depolarization activities. Protoplasts of S. pyogenes were used to investigate carvacrol's effects on the membrane, followed by gel electrophoresis. The carvacrol-treated protoplasts were examined by transmission electron microscopy (TEM) to observe ultrastructural morphological changes. The fluidity of the cell membrane was measured by steady-state fluorescence anisotropy. Thin-layer chromatographic (TLC) profiling was conducted to study the affinity of carvacrol for membrane phospholipids. Results: Increased membrane permeability and decreased membrane potential from FCM and electron microscopy observations revealed that carvacrol killed the bacteria primarily by disrupting membrane integrity, leading to whole-cell lysis. Ultra-structural morphological changes in the membrane induced by carvacrol over a short period were confirmed using the S. pyogenes protoplast and membrane isolate models in vitro. In addition, changes in the other biophysical properties of the bacterial membrane, including concentration- and time-dependent increased fluidity, were observed. TLC experiments showed that carvacrol preferentially interacts with membrane phosphatidylglycerol (P.G.), phosphatidylethanolamine (P.E.), and cardiolipins (CL). Conclusions: Carvacrol exhibited rapid bactericidal action against S. pyogenes by disrupting the bacterial membrane and increasing permeability, possibly due to affinity with specific membrane phospholipids, such as P.E., P.G., and CL. Therefore, the bactericidal concentration of carvacrol (250 µg/mL) could be used to develop safe and efficacious natural health products for managing streptococcal pharyngitis or therapeutic applications.